International agricultural development (Johns Hopkins University Press, 1998)
The book takes into account recent developments in international agricultural development, especially as these affected the role of the state, markets, and other institutions in development. The authors deal with topics such as market failures, food insecurity, rural poverty, environmental degradation, income and asset inequality, fiscally sustainable organizations, the changing roles of the public and private sector in research, and input and output marketing systems.